2022
DOI: 10.3389/fphar.2022.1039867
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance of triazole antifungal agents: Analysis of the FDA adverse event reporting system (FAERS) database

Abstract: Triazole antifungal drugs (TAD) are widely used to treat invasive fungal infections due to their broad antifungal spectrum and low toxicity. Despite their preference in the clinic, multiple Adverse Events (AE) are still reported each year. Objective: We aimed to characterize the distribution of Adverse Events associated with Triazole antifungal drugs in different systems and to identify Important Medical Events (IME) signals for Triazole antifungal drugs. Methods: The U.S. Food and Drug Administration Adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Moreover, there were only one cardiac PT associated with isavuconazole, and no new cardiac PTs in this study. A study conducted by Zhou et al (2022) analyzed the distribution of AEs associated with TAAs in different SOCs from 2012 Q4 to 2022 Q1, and this analysis about the top 30 IMEs induced by TAAs based on all other drugs as analysis contexts showed that the number of the observed significant cardiac PT signals for fluconazole, voriconazole, itraconazole, posaconazole, and isavuconazole was 3, 4, 5, 4, and 1, respectively. Consistent with our results, it showed that isavuconazole had less cardiac PT signals compared to the other four TAAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, there were only one cardiac PT associated with isavuconazole, and no new cardiac PTs in this study. A study conducted by Zhou et al (2022) analyzed the distribution of AEs associated with TAAs in different SOCs from 2012 Q4 to 2022 Q1, and this analysis about the top 30 IMEs induced by TAAs based on all other drugs as analysis contexts showed that the number of the observed significant cardiac PT signals for fluconazole, voriconazole, itraconazole, posaconazole, and isavuconazole was 3, 4, 5, 4, and 1, respectively. Consistent with our results, it showed that isavuconazole had less cardiac PT signals compared to the other four TAAs.…”
Section: Discussionmentioning
confidence: 99%
“…Many adverse events (AEs) have been reported in their postmarketing application, mainly including hepatotoxicity, gastrointestinal reaction, renal impairment, rash, and cardiac disorders (Amsden and Gubbins, 2017;Shen et al, 2022;Yu and Liao, 2022;Zhou et al, 2022). Among these, cardiac disorders were a significant systemic organ class (SOC) signals for important medical events (IMEs) induced by TAAs (Zhou et al, 2022). Cardiac disorders are common clinical conditions associated with high mortality rates (Shinomoto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, potential safety concerns might arise in everyday clinical practice that were not evident during the more controlled and structured environment of clinical trial evaluations [28]. Therefore, postmarketing surveillance and real-world evidence play a crucial role in continuously monitoring the safety and effectiveness of medications once they are in widespread use [29][30][31]. The analysis of pharmacovigilance for a drug, utilizing postmarketing safety databases like the FAERS, plays a crucial role in the ongoing management of risks by detecting safety signals that may not have been identified during the drug's clinical development phase [10,14,[32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%